2012
DOI: 10.1128/ec.00149-12
|View full text |Cite
|
Sign up to set email alerts
|

A Detoxifying Oxygen Reductase in the Anaerobic Protozoan Entamoeba histolytica

Abstract: ABSTRACTWe report the characterization of a bacterial-type oxygen reductase abundant in the cytoplasm of the anaerobic protozoan parasiteEntamoeba histolytica. Upon host infection,E. histolyticais confronted with various oxygen tensions in the host intestine, as well as increased reactive oxygen and nitrogen species at the site of local tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
44
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 46 publications
5
44
0
Order By: Relevance
“…Like the WT protein (11), all the EhFdp1 variants were isolated in the oxidized state with UV-visible absorption bands with maxima at 377 and 456 nm, characteristic of the flavin moiety. The FMN reduction potentials were determined by anaerobic redox titrations (Fig.…”
Section: Biochemical Properties Of Wt and Mutated Ehfdp1-thementioning
confidence: 99%
See 4 more Smart Citations
“…Like the WT protein (11), all the EhFdp1 variants were isolated in the oxidized state with UV-visible absorption bands with maxima at 377 and 456 nm, characteristic of the flavin moiety. The FMN reduction potentials were determined by anaerobic redox titrations (Fig.…”
Section: Biochemical Properties Of Wt and Mutated Ehfdp1-thementioning
confidence: 99%
“…Direct sequencing confirmed that only the desired mutations were inserted. Expression in E. coli BL21(DE3) Gold cells and purification of wild-type (WT) and mutated EhFdp1 were carried out as previously described (11). Because the physiological electron donor to the E. histolytica EhFdp1 is presently unknown, we used an artificial reducing system from E. coli: the flavorubredoxin reductase (FlRd-Red) and the rubredoxin domain (Rd-D) of FlRd, that were expressed and purified as described in Ref.…”
Section: Structure Prediction Of the E Histolytica Ehfdp1 And Aminomentioning
confidence: 99%
See 3 more Smart Citations